2013
DOI: 10.1016/j.jcf.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic expression of the 3120+1G>A mutation in non-Caucasian children with cystic fibrosis in South Africa

Abstract: Failure to thrive and a diagnosis of protein energy malnutrition (kwashiorkor) are the common presenting features of CF in children with the 3120+1G>A mutation. Meconium ileus is a rare presenting feature of CF in black and mixed race children with this deletion in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…protein energy malnutrition, HIV infection and tuberculosis, which affect the black population in SA to a considerable extent. [3] Another reason may be a high threshold for suspicion, as CF is not common in this population. One study in a Western country showed that features associated with late diagnosis were pancreatic insufficiency and certain genotypes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…protein energy malnutrition, HIV infection and tuberculosis, which affect the black population in SA to a considerable extent. [3] Another reason may be a high threshold for suspicion, as CF is not common in this population. One study in a Western country showed that features associated with late diagnosis were pancreatic insufficiency and certain genotypes.…”
Section: Discussionmentioning
confidence: 97%
“…These populations commonly present with failure to thrive and protein energy malnutrition. [3] Early diagnosis of CF prevents severe malnutrition and improves long-term growth. [4] In CF, nutrition and growth are determinants of lung health and, ultimately, survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve African countries had published a total of 26 reports of molecular investigations into the cause of CF-Morocco, [38][39][40] Algeria, [41][42][43] Tunisia, 40,41,[44][45][46] Libya, 47 Egypt, [48][49][50] Sudan, 18 Rwanda, 51 Senegal, 52 Cameroon, 52,53 Namibia, 54 Zimbabwe, 55 and South Africa, 2,37,[55][56][57][58][59][60] -for a total of 2,344 chromosomes screened. Only two publications met our inclusion criteria while also screening non-CF patients; 39,58 in these instances, we included only the data obtained from the CF patients described in these publications.…”
Section: Resultsmentioning
confidence: 99%
“…36 The estimated South African cost may reflect the impact of delayed diagnosis on treatment costs-CF patients are, on average, diagnosed at age 13 months. 37 Delayed diagnosis has been shown to have a negative impact on nutrition, growth, and lung function. CF patients who receive a delayed diagnosis also tend to be hospitalized more frequently, with more severe pulmonary exacerbations, increasing treatment costs.…”
Section: Cf Patient Survivalmentioning
confidence: 99%